May Day and the Moon - Green, Cheryl; Miller, Grant (Critical Disability Discourses, 2019)
"May Day and the Moon" is a playful audio exploration of childhood dreams of adult work. The storyteller, Grant Miller, is a non-binary queer disabled white person born with disabilities and having acquired disability later in life as well. Unlike mainstream disability-related stories, Grant never describes their disability nor names any diagnoses. This is done to invite audiences to trust the storyteller and to disinvite the possibility of an objectifying medical gaze. We approach the idea of work indirectly in a sound-rich audio story, challenging the standard interview format. Rather than overtly discuss unemployment, underemployment, and capitalism, the story focuses on the lack of disabled role models in the working world and lack of family encouragement to consider pursuing adult work. The story concludes with a celebration of the innovation and creativity that Grant has incorporated into their self-empowered, self-directed, joy-filled artistic life.